Hubungan Suhu dan Kelembapan dengan Keberadaan Jentik Nyamuk Aedes aegypti pada Kasus DBD di Kecamatan Tembalang Kota Semarang - Alfan Afandi; Kartika Dian Pertiwi; Berliana Indah Septia (CV. ALIM'SPUBLISHING, 2026)
Dengue Hemorrhagic Fever (DHF) remains a significant public health problem in tropical countries, including Indonesia. The presence of Aedes aegypti larvae is an important indicator of dengue transmission risk and is influenced by environmental factors, particularly temperature and humidity. This study aimed to analyze the relationship between temperature and humidity and the presence of mosquito larvae in Meteseh Village, Tembalang District, Semarang City. This analytical observational study employed a cross-sectional design involving 100 households selected through quota sampling. Data were collected through direct observation and measurement of temperature and humidity using a thermo-hygrometer, then analyzed using the Chi-square test. The results showed a significant association between temperature and the presence of mosquito larvae (p=0.000), while humidity was not significantly associated with larvae presence (p>0.05). Temperature was identified as a more influential environmental factor in supporting mosquito larvae existence than humidity in the study area. These findings highlight the importance of environmental-based vector control strategies, particularly through management of microhabitat temperature conditions, to support dengue prevention.